A conceptual framework for managing information flow in innovation systems. (12th March 2007) - Temel, Tugrul
This study introduces a framework for managing information flow in innovation systems. An organisation's capacity to receive information, to share it with others and to learn from it is assumed to be the key factor that shapes the flow patterns and, hence, the performance of the innovation system concerned. The framework is applied to characterise the information structure underlying the agricultural innovation system of Azerbaijan and to develop an information strategy for the system to accelerate the information flow. The key institutions required to promote and support an effective flow of information in innovation systems are also discussed.